Iron-catalyzed direct julia-type olefination of alcohols - Landge, Vinod G.; Babu, Reshma; Yadav, Vinita; Subaramanian, Murugan; Gupta, Virendrakumar; Balaraman, Ekambaram (Journal of Organic Chemistry, 2020)
Herein, we report an iron-catalyzed, convenient, and expedient strategy for the synthesis of styrene and naphthalene derivatives with the liberation of dihydrogen. The use of a catalyst derived from an earth-abundant metal provides a sustainable strategy to olefins. This method exhibits wide substrate scope (primary and secondary alcohols) functional group tolerance amino, nitro, halo, alkoxy, thiomethoxy, and S- and N-heterocyclic compounds) that can be scaled up. The unprecedented synthesis of 1-methyl naphthalenes proceeds via tandem methenylation/double dehydrogenation. Mechanistic study shows that the cleavage of the C-H bond of alcohol is the rate-determining step.